Effect of mixed-phase TiO2 doped with Ca2+ on charge transfer at the TiO2/graphene interface. (1st August 2022) - Cai, Ding; E, Tao; Yang, Shuyi; Ma, Zengying; Li, Yun; Liu, Lin; Wang, Daohan; Qian, Jianhua
Highlights: The Ca 2+ -doped mixed-phase TiO2 was prepared by hydrothermal method, and the Ca 2+ -doped mixed-phase TiO2 /graphene composites were synthesized by one-step self-assembly method. The synergistic effect of mixed-phase TiO2 and Ca 2+ significantly enhances the carrier concentration as well as the TiO2 /G interfacial transfer rate. Such Ca 2+ -doped mixed-phase TiO2 /graphene composites have promising applications in the field of conductive coatings. Abstract: Conductive coatings can effectively prevent fires and explosions caused by electrostatic sparks, ensuring safety in production and life. However, the commonly used TiO2 has poor electrical conductivity. Herein, we employ mixed-phase TiO2 based on Ca/TiO2 /graphene and dope Ca 2+ into the TiO2 lattice. The results show that the Ca 2+ -doped mixed-phase TiO2 /graphene composite (T-G-Ca) has excellent electrical conductivity with a minimum resistivity of 0.082 Ω cm, which is 7 times higher than the electrical conductivity of single-crystal Ca/TiO2 /graphene (0.58 Ω cm). The improved electrical conductivity is attributed to the easier electron-hole separation of mixed-phase TiO2 than single-crystal TiO2, especially the synergistic effect with Ca 2+ that significantly increases the carrier concentration. Meanwhile, a new three-dimensional conductive path (Ca-O-C) is formed between graphene and Ca 2+ -doped mixed-phase TiO2, which effectively increases the interfacial charge transfer rate. It is the significant enhancement of both carrier concentration and charge transfer that leads to a significant decrease in resistivity. Therefore, T-G-Ca has potential applications in the field of conductive coatings. Graphical abstract: Image, graphical abstract